Response of tall buildings to weak long distance earthquakes. - Brownjohn, James Mark William (Earthquake engineering & structural dynamics.)
In the last decade, two tall buildings in Singapore were instrumented with accelerometers and anemometers for the original purpose of identifying the characteristics and effects of wind loading. During the monitoring it became clear that the largest acceleration responses should result from ground motions due to earthquakes having magnitudes between 6 and 8 and epicentres at least 350 km distant. The paper describes the strategy for identifying and capturing the signals from distant tremors, which depends on tracking the RMS response levels in the second vibration mode. Characteristics of some recorded signals are given. While response levels are generally small, the frequency content coincides with the range of fundamental mode frequencies for high rise residential buildings. The validity of using a tall building as a 'weak motion' seismograph is discussed by considering the mode shape of the building and the measured transfer function between basedment and roof responses.